Relationship between morphological measurements of trunk in Erythrina americana Miller and yield of edible foliage - Oliva Hernández, Jorge; López Herrera, María Aurelia; Castillo Linares, Erika Belem (Ecosistemas y Recursos Agropecuarios, 2021)
The aim of this study was to analyze the relationship ofdiameter and height of Erythrina americana tree with the foliage yield ata regrowth age of 90 days. Forty-seven trees with height of 1.6 m ± 0.2m, diameters of 0.085 ±0.021 and 0.065 ± 0.018 at a height of 0.20m and 1.3 m from soil respectively were used. The relationship betweenheight and diameters of the tree with the dry matter yield (DMY) tree-1was determined with correlation process. The variation in DMY tree-1 wasdetermined through multiple regression. Tree height and diameters at 0.20and 1.3 m had a positive relationship with DMY tree-1 (p < 0.05 and p